The inner world of research : on academic labor - Svallfors, Stefan (Anthem Press, 2020)
The Inner World of Research is a book about the joys and miseries of life as a researcher. Dealing with essential but rarely mentioned topics in the everyday life of a researcher, it focuses in particular on the role of emotions and social relations in research. It stretches from the individual researcher, to the 'micro-cosmos' of the research team, to the broader policy environment in which research takes place. Though based on autobiographical material from Stefan Svallfors' long career as a leading social scientist, the book also derives from extended interviews with researchers from a variety of disciplines, and with authors, artists and musicians. It delves into the mysteries of creativity; the joys and frustrations of collaboration; and the role of fear, anger and boredom in the life of a researcher.